The Influence of Audit Quality and Fiscal Loss Compensation on Tax Avoidance - Believer (JEKAMI Journal of Accounting, 2021)
The purpose of this study is a quantitative study with the aim to determine the effect of audit quality and fiscal loss compensation on tax avoidance. This sample was taken from real estate and property companies listed on the IDX. The type of data used in this study is quantitative data obtained from financial statements contained in the official website of the Indonesia Stock Exchange. Data collection is carried out using documentation techniques, including collection techniques by recording and copying financial statements. In this study, the data sources used in data collection include secondary data. The results of the study show that data using statistical calculations through the application of Econometric Views (Eviews) version 12 regarding the effect of audit quality and loss compensation on tax avoidance which has been discussed in the previous chapter, the authors draw an important conclusion that audit quality affects tax avoidance while tax loss compensation does not affect tax evasion, tax evasion compensation. So the company must pay attention to the audit quality variables in examining a company's tax avoidance, fiscal loss compensation is the obligation of a company to pay taxes.